TINGKAT KEBAHAGIAAN MAHASISWA JAKARTA DALAM MENGONSUMSI KONTEN “HOW TO BE RICH” - Natiyan Fajar Nugroho; Untung Subroto; Vergio Gary; Anastasya Syafira Miranda (STKIP Subang, 2026)
This study aims to describe the consumption of “How To Be Rich” content and its relationship to the happiness of university students aged 17–27 in Jakarta. The research stems from the increasing exposure to financial content on social media, which may influence perceptions of success and happiness. A descriptive quantitative method was used through an online questionnaire with 106 respondents. Happiness was measured using a modified Oxford Happiness Questionnaire. Results showed that most participants had a high level of happiness after consuming the content. Male students tended to feel more motivated and optimistic than female students, though the difference was not significant. The findings suggest that financial content can positively influence student happiness when approached with critical understanding.